The African novel of ideas : philosophy and individualism in the age of global writing - Jackson, Jeanne-Marie (Princeton University Press, 2021)
"This study focuses on the role of the philosophical novel-a genre that favors abstract concepts, or "thinking about thinking," over style, plot, or character development-and the role of philosophy more broadly in the intellectual life of the African continent. As philosophy over the past century of African intellectual life has evolved from the mainstream to the fringe, the African novel has gained in global market share and cachet. If postcolonial African writers of the 1950s to the 1980s were enshrined as voices of resistance to colonial regimes, the celebrated new wave of African writing now leads efforts to represent the immediacies of African experience: Africa is no longer a concept or cause but a complex web of real places, histories, and lives. The African Novel of Ideas examines philosophy in the African novel from the Gold Coast, to Zimbabwe, through Burundi, Uganda, and South Africa. By tracing the ways in which African writers such as J.E. Casely-Hayford, Stanley Samkange, Ama Ata Aidoohave, and Jennifer Makumbi have sought to reconcile a hunger for deep contemplation with the demands of their social situation as its canvas expands, Jackson offers a new way of reading and understanding African literature. As she examines the relationship between literary history and narrative technique, Jackson argues that the "postcolonial" African novel is an intermediate form between colonialism and new forms of African fiction more concerned with regional political and philosophical debates than to the traditions and narratives of European literary history"--